Weed management in ajwain (Trachyspermum ammi L.) - R S Mehta, R D Meena, R L Meena, S S Meena (Journal of Spices and Aromatic Crops, 2015)
A field experiment was conducted to find out a suitable and economical method of weed management in ajwain. The experiment was laid in randomized block design with three replications. Based on the two year study, it was found that besides weed free treatment, significantly higher plant height, number of primary, secondary branches, number of leaves, number of nodes and dry matter accumulation plant-1 at (60 DAS, 90 DAS and at harvest) were recorded with the pre-emergence application of oxadiargyl @75 g ha-1 + one hand weeding at 45 days after sowing (DAS) and pendimethalin @1 kg ha-1 + one hand weeding at 45 DAS. Yield attributes like number of umbels plant-1, number of umbellate pant-1, number of seeds umbel-1, umber of seed umbellate-1 and test weight as well as seed and straw yields of ajwain were also higher with the above two treatments. After weed free treatment, the lowest dry weight of weed at harvest, weed index and highest weed control efficiency were obtained with pre-emergence (PE) application of oxadiargyl @75 g ha-1 + one hand weeding at 45 DAS. The highest gross returns and net returns per hectare were obtained in weed free treatment. This was followed by pre-emergence application of oxadiargyl @75 g ha-1 + one hand weeding at 45 DAS, which recorded the highest B: C ratio (2.62).